The effect of non-audit services on audit quality - Nyberg, Otto (My University, 2014)
Recently, there has been growing interest by regulators to review the effects of non-audit service fees on audit quality. This is done because non-audit services poses a threat to auditor independence as the auditor might have to audit his or her own work. It is the aim of this thesis to achieve a comprehensive understanding on whether non-audit service fees affect audit quality, and whether auditor independence is impaired by the presence of these services. This thesis consist two sections. First section of this thesis introduces previous academic studies on audit quality and non-audit services. Second section constitutes the empirical part of this study, in which modified Jones model is used in order to investigate the relation between non-audit services and audit quality in Finnish publicly listed companies between 2010 and 2012. In spite of great interest, empirical evidence over the association between non-audit services, audit quality and auditor independence has yielded mixed results. However, a great number of studies proposing non-audit fees to have a positive effect on audit quality could be viewed suggestive while making conclusions. Also, criticism towards the results of studies proposing non-audit fees to have negative effects on audit quality e.g. Frankel et al. (2002) could be utilized when analysing this relationship. Thus, general perception amongst academics seems to be in favour of provision of non-audit services to audit clients. Based on the results introduced in the second part of this study, no associations were found between measures of audit quality and non-audit fees. However, results indicate that two control variables used, are associated with audit quality. Cash flow from operations seem to have a negative association with audit quality, whereas, a positive association is discovered between audit quality and growth rate of net sales. Nevertheless, these results can only be viewed as tentative due to a number of reasons e.g. limited number of companies listed in Finland and hence, included into the regression model. It can be concluded that further research could be utilized to further investigate the relationship between audit quality and non-audit fees.
Keywords: non-audit services (NAS); independence; audit quality; earnings management; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|